2014
DOI: 10.1155/2014/451674
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Stimulation at the ST36 Acupoint Protects against Sepsis Lethality and Reduces Serum TNF Levels through Vagus Nerve‐ and Catecholamine‐Dependent Mechanisms

Abstract: Electrical vagus nerve (VN) stimulation during sepsis attenuates tumor necrosis factor (TNF) production through the cholinergic anti-inflammatory pathway, which depends on the integrity of the VN and catecholamine production. To characterize the effect of electroacupuncture at ST36 (EA-ST36) on serum TNF, IL-6, nitrite, and HMGB1 levels and survival rates, based on VN integrity and catecholamine production, a sepsis model was induced in rats using cecal ligation and puncture (CLP). The septic rats were subsequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 21 publications
(33 reference statements)
0
36
0
Order By: Relevance
“…Here, we introduced it for POI treatment because a growing body evidence indicates that EA regulates the GI function by exciting vagus nerve system and might produce anti-inflammatory effect5253. If EA could activate vagus nerve system before surgery, it might prevent POI via the cholinergic anti-inflammatory pathway such as previous study.…”
Section: Discussionmentioning
confidence: 98%
“…Here, we introduced it for POI treatment because a growing body evidence indicates that EA regulates the GI function by exciting vagus nerve system and might produce anti-inflammatory effect5253. If EA could activate vagus nerve system before surgery, it might prevent POI via the cholinergic anti-inflammatory pathway such as previous study.…”
Section: Discussionmentioning
confidence: 98%
“…Only 6 studies [51,52,61,64,75,77] reported using adult animals, 16 studies [30,34,38,40,49,50,53,57,62,65,68,69,73,[78][79][80] had no statement about animals' age, and the remaining 33 studies reported the specific age of the animals.…”
Section: Experimental Animalsmentioning
confidence: 99%
“…Urethane [30, 31, 34-38, 40, 42-45, 47-50] was used in 16 studies to induce anesthesia, pentobarbital [41, 63, 65, 66, 72-74, 76, 77, 80, 81] was used in 11 studies, ketamine [32,57,58,62] was used in 4 studies, chloral hydrate [29,78] was used in 2 studies, and xylazine hydrochloride [33] and isoflurane [64] were used in 1 study, respectively. Ketamine combined with Suxinmian [54-56, 59-61, 79], midazolam [67,70,71], xylazine [21,69], and urethane [39,46] were used in 7, 3, 2, and 2 studies, respectively. While the remaining 5 studies [51-53, 68, 75] had no statement about anesthetics.…”
Section: Sepsismentioning
confidence: 99%
“…Electrical stimulation of the sciatic nerve significantly reduced circulating levels of cytokine in a murine endotoxemia model in a vagus nerve dependent manner. Blocking of vagus nerve activity with either pharmacological antagonists or surgical ablation suppressed the inhibitory effects of electrical stimulation (5153). In a collagen-induced arthritis model, electrical stimulation of the sciatic nerve significantly reduced arthritis incidence, attenuated inflammatory cytokine levels, and prevented joint destruction (54).…”
Section: Vagus Nerve-adrenal Reflexmentioning
confidence: 99%